An Algorithm of Fractal Tree Generate Base on Controllable Random Transform - Jiang, Lin; Guo, Xianchun; Lu, Ling (Computer Modeling and Simulation Proceedings, 2009)
An algorithm of fractal tree is hot research area in nature scenery simulation. We present a generate algorithm of fractal tree by use a controllable random transform method. This method base on fractal theory, controls some parameters of fractal tree generating in a random scope, which parameters including coordinates, length of tree branch, angle of tree branch transfer, thickness of trunk, color of render. Experiment show fractal tree rendered has a third dimension, although our render method is planar. Our algorithm guarantees the worst-case cost of O(B*level) for rendering a fractal tree, where B is numbers of tree branch and level is numbers of node on each branch.